(untitled) (Research, Society and Development, 2023)
The Hansen’s bacillus is highly infectious, presents physical disabilities, infers late detection of the disease, presenting consequent damage to its carriers, including social and psychological issues. The objective was to analyze the clinical and epidemiological profile of leprosy patients in Imperatriz-MA between 2015 and 2021. This is an epidemiological, retrospective, cross-sectional and descriptive study, which concerns the research with secondary data of leprosy cases with search in Imperatriz-MA, in the period from 2015 to 2021. The data were collected on the website of the Department of Informatics of the Unified Health System (DATASUS), from the Information System of Notifiable Diseases (SINAN). Therefore, the information is available in the health information section (TABNET), in the epidemiology and morbidities option. In the period from 2015 to 2021, 1,256 patients with leprosy were registered in the municipality of Imperatriz. There was a prevalence in the male gender (59, 63%), in the age group of 40 to 49 years (17.91%), ethnicity/color brown (53.90%) and, regarding education, incomplete elementary school (45.46%). Regarding the clinical form present in this study, most patients presented the dimorphic form (54.77%), followed by the Virchowian form (20.22%). Therefore, there were underreported cases in the period studied due to the pandemic of COVID-19, even so, there is a need for screening of the disease, early diagnosis, to reduce injuries, since it affects the socioeconomic factors of the individual.